Surgical outcomes of a randomized controlled trial compared robotic versus laparoscopic adrenalectomy for pheochromocytoma. Issue 10 (October 2020) - Ma, Wenming; Mao, Yongxin; Zhuo, Ran; Dai, Jun; Fang, Chen; Wang, Chenghe; Zhao, Juping; He, Wei; Zhu, Yu; Xu, Danfeng; Sun, Fukang
Abstract: Background: Robotic adrenalectomy for pheochromocytoma is increasingly popular because of the advantage that have been proved by some researchers recently. However, prospective randomized clinical trials comparing robotic assisted laparoscopic adrenalectomy (RA) with traditional laparoscopic adrenalectomy (LA) for pheochromocytoma are rare. The aim of this study is to compare perioperative outcomes of RA versus LA for pheochromocytoma prospectively. Methods: From March 2016 to April 2019, all patients with pheochromocytoma suitable for laparoscopic adrenalectomy were assigned randomly to RA or LA. The primary endpoint was the operative (exclude docking time) time. Secondary endpoints were estimated blood loss and postoperative recovery. Demographics and perioperative data were prospectively collected. Results: A total of 140 (RA 70, LA 70) patients were enrolled in this prospective research. The following significant differences were identified in favor of RA: shorter median operative (exclude docking time) time (92.5 vs 122.5 min, P  = 0.007), however, RA group has higher total hospitalization cost (8869.9 vs 4721.8 $, P < 0.001). Demographics and other perioperative outcomes were similar in both groups. The RA group showed a significant lower blood loss and operative (exclude docking time) time compared with LA group ( P  < 0.05) for patients with high Nor-Metanephrine (NMN). Conclusions: Both RA and LA for pheochromocytoma are safe and effective. Patients with high NMN can benefit from less blood loss and operative time when a robotic surgery system was used, but RA has a significant higher cost.